An open-label, randomized, single intravenous dosing study to investigate the effect of fixed dose combinations of tenofovir/lamivudine or atazanavir/ritonavir on the pharmacokinetics of remdesivir in Ugandan healthy volunteers (RemTLAR) - Walimbwa, Stephen Ian; Kaboggoza, Julian Paul; Waitt, Catriona; Byakika-Kibwika, Pauline; D'Avolio, Antonio; Lamorde, Mohammed (Research Square, 2021)
Remdesivir is a novel broad-spectrum antiviral therapeutic with activity against several viruses that cause emerging infectious diseases. The purpose of this study is to explore how commonly utilized antiretroviral therapy (tenofovir disoproxil fumarate /lamivudine [TDF/3TC] and atazanavir/ritonavir [ATV/r]) influence plasma and intracellular concentrations of remdesivir.
Keywords: Remdesivir; COVID-19; Ebola; HIV; Atazanavir; Ritonavir; Tenofovir; Lamivudine; Drug-drug interactions